Neural Model of Transmission Channel in 60 Ghz ISM Band - Kotol, Martin (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2016)
In this paper, methodology of estimating parameters of a wireless transmission channel inside a car is presented. The work is focused on the utilization of artificial neural networks for channel modelling in the frequency range from 55 GHz to 65 GHz. Promising results have been reached by a feed-forward neural network and a radial basis function neural network. In order to train the networks, a wireless transmission was carefully measured in a testing car. Measured data were properly processed to be used both for training neural networks and validating neural models.
Keywords: Artificial neural network; feed-forward network; radial basis function network; parameter estimation; in-car wireless transmission